Lateral intra-extraspinal cervical schwannomas: partial versus total resection - Stefanović, Ivan; Stefanovic, Stefan (Central European journal of medicine, 2012)
The study involved 27 lateral cervical schwannomas surgically treated in the last 40 years utilizing either partial or total resection. The study aims to compare the results of total and partial resection of spinal lateral schwannoma and to assess the values of partial resection of large lateral cervical schwannomas. We performed a retrospective analysis of 27 patients operated for lateral cervical schwannomas in the period 1971-2010, out of which 11 had partial resection. The average follow-up of the patients was 136.4 months, comparing pre- and postoperative clinical picture, time to relapse, dynamics of yearly growth of schwannomas, and the need for re-resection. The average period of preoperative complaint in lateral cervical schwannomas was 19.6 months. Unilateral cervicobrachialgia as a manifestation of radiculopathy was observed in 85% of LCSs, and, was, as a rule the first symptom of the disease. Surgical treatment of 27 patients with LCSs resulted in recovery or improvement of complaints in 80% of cases. The treatment effect did not depend on the degree of resection. Reoperation was done, on average, 16.3 years after partial resection. The residues of lateral cervical schwannomas stopped growing 15 years after partial resection and underwent cystic degeneration. Partial resection of lateral cervical schwannomas is an excellent alternative to total resection, not only for the elderly or in cases of increased surgical risk, but also as a method of choice since it is more readily available to a larger number of surgeons and associated with low percentages of surgically relevant relapses and high percentages of improvement.
Online erschienen: 24.11.2011
Gesehen am 20.09.2018